The physiological response of farmed ballan wrasse (Labrus bergylta) exposed to an acute stressor - Leclercq, Eric; Davie, Andrew; Migaud, Herve (Aquaculture, 2014)
Ballan wrasse (Labrus bergylta) aquaculture has emerged as a strategic development for the sustainable control of sea-lice (Lepeophtheirus salmonis) in the European Atlantic salmon (Salmo salar) industry. Farmed ballan wrasse juveniles were exposed to a standard acute stressor (1min air exposure) and the patterns of change in blood haematocrit, plasma cortisol, glucose and lactate were described over a 24h period using newly validated analytical methods in that species. Plasma cortisol concentrations were relatively high and rose from a resting basal level of 60.8±5.5ng·ml-1 to a peak concentration of 284.3±26.7ng·ml-1 (3.7-fold increase) 30min post stress exposure. Cortisol was found to be the most sensitive indicator of stress followed by plasma glucose showing 83.9% increase from a resting basal level of 2.2±0.1mmol·l-1 30min post-stressor. The use of handheld metres for monitoring glucose and lactate levels was successfully validated against the reference spectrophotometric methods for on-site assessment. Validation of the methods and identification of the most sensitive stress indicators are expected to assist in the identification of adverse conditions and best rearing practices for this emerging new aquaculture species.